Deviation of Communication Ethics in Hospitals During the Covid 19 Pandemic Period March 2020 to January 2021 (Case Study at Menteng Mitra Afia Hospital) - RINALDI, Enrico Adhitya; LILIWERI, Alo; DUA, Mikhael; MULYASANTOSA, Nandang (International Journal of Environmental, Sustainability, and Social Science, 2023)
This study aims to analyze the Deviation of Communication Ethics seen from Medical Action Management Response and Communication Contravention. In this study, data was collected through an interview method with 10 health workers at Menteng Mitra Afia Hospital and 1 external resource person. The problem in this research is "Ethical Deviation and crisis communication at Menteng Mitra Afia Hospital in Central Jakarta in handling the crisis due to the Covid-19 outbreak which requires speed of action but is highly dependent on the government so that it can become a guide in the future". In this study, data were collected through an interview method with 10 health workers at Menteng Mitra Afia Hospital and 1 external resource person using the Research Paradigm to find out various medical actions in crisis situations, forms or types of ethical deviations, examine management responses and formulate policy models. Then analyze the data obtained in the form of Inductive Analysis, this analysis uses qualitative research methods, induction and case studies. Where one research begins with specific observations and measurements. By starting to detect patterns and regularities,formulate some tentative hypotheses that we can explore and finally develop some conclusions or general theories and concepts. The results of this study are that there are problems with the availability of facilities and infrastructure that have the potential to affect deviations in communication ethics, communication problems originating from human resources, doctors and health workers, and problems with deviations from the service system that have the potential to affect communication ethics